Motor Cortex Stimulation for Pain Relief: Do Corollary Discharges Play a Role? - Brasil-Neto, Joaquim P. (Frontiers in Human Neuroscience, 2016)
Both invasive and non-invasive motor cortex stimulation techniques have been successfully employed in the treatment of chronic pain, but the precise mechanism of action of such treatments is not fully understood. It has been hypothesized that a mismatch of normal interaction between motor intention and sensory feedback may result in central pain. Sensory feedback may come from peripheral nerves, vision and also from corollary discharges originating from the motor cortex itself. Therefore, a possible mechanism of action of motor cortex stimulation might be corollary discharge reinforcement, which could counterbalance sensory feedback deficiency. In other instances, primary deficiency in the production of corollary discharges by the motor cortex might be the culprit and stimulation of cortical motor areas might then be beneficial by enhancing production of such discharges. Here we review evidence for a possible role of motor cortex corollary discharges upon both the pathophysiology and the response to motor cortex stimulation of different types of chronic pain. We further suggest that the right dorsolateral prefrontal cortex, thought to constantly monitor incongruity between corollary discharges, vision and proprioception, might be an interesting target for non-invasive neuromodulation in cases of chronic neuropathic pain.